Challenges of diagnosis and management of giant cell arteritis in general practice: a multimethods study - Helliwell, Toby (BMJ Open, 2018)
BACKGROUND: In the UK, general practitioners (GPs) are usually the first medical contact for patients with suspected giant cell arteritis (GCA). While rare, it is critical not to miss, as delayed treatment can lead to significant complications including permanent visual loss. To date, little is known about the approach and challenges to diagnosis and management of GCA by GPs. OBJECTIVE: To investigate the diagnosis and management of patients with suspected GCA in UK general practice. DESIGN AND PARTICIPANTS: A multimethods approach was taken, comprising a postal survey of 5000 randomly selected UK GPs and semistructured telephone interviews of 24 GPs from across the UK. SETTING: UK general practice. RESULTS: 1249 questionnaires were returned. 879 responders (70%) indicated that they had diagnosed and managed a patient with GCA. A variety of clinical features were used to identify GCA. 21.9% suggested that they would exclude GCA as a diagnosis if headache was absent and around one-third do not routinely initiate glucocorticoid treatment prior to referral. Significant regional variations in referral pathways were reported. Thematic analysis of interview transcripts highlighted fears relating to a missed diagnosis of GCA and the non-specific nature of early GCA presentation. Accessing specialist care was highlighted as challenging by many GPs and that a national standard fast-track pathway is lacking to support this patient group. Additionally there were significant concerns regarding potential adverse effects relating to long-term treatment with glucocorticoids. CONCLUSION: GPs appear to over-rely on headache to identify GCA and marked geographical differences in management, with conflicting referral pathways and difficulties in accessing appropriate services exist in the UK. A national standard for fast-tracking patients with suspected GCA to relevant specialists would be beneficial to improve care and outcomes for patients with GCA.